Annexin A1 Tethers Membrane Contact Sites that Mediate ER to Endosome Cholesterol Transport - Eden, Emily R. (Dev Cell, 2016)
Membrane contact sites between the ER and multivesicular endosomes/bodies (MVBs) play important roles in endosome positioning and fission and in neurite outgrowth. ER-MVB contacts additionally function in epidermal growth factor receptor (EGFR) tyrosine kinase downregulation by providing sites where the ER-localized phosphatase, PTP1B, interacts with endocytosed EGFR before the receptor is sorted onto intraluminal vesicles (ILVs). Here we show that these contacts are tethered by annexin A1 and its Ca(2+)-dependent ligand, S100A11, and form a subpopulation of differentially regulated contact sites between the ER and endocytic organelles. Annexin A1-regulated contacts function in the transfer of ER-derived cholesterol to the MVB when low-density lipoprotein-cholesterol in endosomes is low. This sterol traffic depends on interaction between ER-localized VAP and endosomal oxysterol-binding protein ORP1L, and is required for the formation of ILVs within the MVB and thus for the spatial regulation of EGFR signaling.